(untitled) (Indian Journal of Animal Production and Management, 2024)
The present study was conducted using 23 years of data pertaining to 1223 lactations of Murrah buffaloes under the suckling system of calf rearing at Cattle and Buffalo Farm (Livestock Production and Management Section), ICAR-Indian Veterinary Research Institute, Izatnagar (Bareilly), Uttar Pradesh, India. The milk yields per kg of live body weight (MY/BW) were estimated by dividing monthly milk yields (MMY) in lactation by respective average monthly live body weights (MLB) of milch buffaloes during 1-13th months of lactation. The effect of the season of calving was studied by considering five seasons i.e. Winter (December February), Spring (March-April), Summer (May June), Rainy (July-September), and Autumn (October-November) and months of caving considered were 1st to 12th months in a year. Season and months of calving showed significant to highly significant differences (P≤0.01/0.05) for milk yields per kg live body weights for most of the months in lactations in Murrah buffaloes.